2014
DOI: 10.1093/carcin/bgu109
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a role of E-cadherin in suppressing liver carcinogenesis in mice and men

Abstract: The cell adhesion molecule E-cadherin has critical functions in development and carcinogenesis. Impaired expression of E-cadherin has been associated with disrupted tissue homeostasis, progression of cancer and a worse patient prognosis. So far, the role of E-cadherin in homeostasis and carcinogenesis of the liver is not well understood. By use of a mouse model with liver-specific deletion of E-cadherin and administration of the carcinogen diethylnitrosamine, we demonstrate that loss of E-cadherin expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…Adherens junction protein E‐cadherin is important for polarization formation of hepatocytes, and inactivation of human E‐cadherin is strongly associated with tumorigenesis and increased cancer invasiveness . It was reported that E‐cadherin decreased immunohistochemically in patients with ARC syndrome .…”
Section: Resultsmentioning
confidence: 99%
“…Adherens junction protein E‐cadherin is important for polarization formation of hepatocytes, and inactivation of human E‐cadherin is strongly associated with tumorigenesis and increased cancer invasiveness . It was reported that E‐cadherin decreased immunohistochemically in patients with ARC syndrome .…”
Section: Resultsmentioning
confidence: 99%
“…A hallmark of EMT is the aberrant expression of E-cadherin (encoded by CDH1 ), which is always linked to the tumorigenesis of many epithelial cancers [29]. E-cadherin is a key factor of cell-cell adhesion junctions in the maintenance of cell polarity and structure.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, specific invalidation of E-cadherin in biliary epithelial cells was associated with portal inflammation and ductular reaction. Consistently, mice invalidated for hepatic E-cadherin that maintain E-cadherin expression in non-hepatocyte cells do not show ductular proliferation and portal fibrosis [12]. Thus, accumulation of bile acids in the portal space may be the first trigger inducing inflammation and proliferation of biliary epithelial cells.…”
mentioning
confidence: 84%
“…The fact that, the number of tumor rises when carcinogenesis is primed in mice deficient for liver E-cadherin, indicates that E-cadherin is mainly involved in the progression of the primary tumors. Consistently, diethylnitrosamine (DEN)-induced HCC tumor growth is accelerated in liver of E-cadherin deficient mice [3,12].…”
mentioning
confidence: 91%